Bhutan Urban Policy Notes : Affordable Housing Policy - World Bank (World Bank, Washington, DC, 2019)
This paper is part of a series of four Urban Policy Notes that provide a critical review on emergent challenges to Bhutan’s increasing urbanization and its ramifications for growth, livability and sustainability in line with the directives of the 12th Five-Year Plan (FYP) and the Vision 2020. The four notes are: (a) Regional Development, (b) Municipal Governance and Finance, (c) Affordable Housing and (d) Urban Resilience. These notes build on the long engagement between the Royal Government of Bhutan (RGoB) and the World Bank on urban issues as well as the experiences of urban operations under Bhutan Urban Development Projects I (1999-2006) and II (2010-2019) and are intended to support the RGoB on key and emerging urban topics and guide Bank’s future analytical and investment support in the urban sector.